Acute inflammation phase proteins in cases of IgE-mediated and IgE-independent atopic dermatitis - A. V. Burdina; V. N. Zorina; N. G. Korotkiy; T. V. Shkolnikova; N. A. Zorin (State Scientific Center of Dermatovenereology and Cosmetology, 2017)
Goal. To determine the blood serum level of α2-macroglobulin (α2-MG), α1-antitrypsin (α1-AT), lactoferrin (LF) and albumin in patients with IgE-mediated and IgE-independent atopic dermatitis (AD). Materials and methods. The authors tested blood serum of 60 adult patients suffering from atopic dermatitis at the exacerbation stage (30 patients with IgE-mediated and 30 patients with IgE-independent atopic dermatitis) and 20 healthy donors in order to determine the level of these proteins by rocket immunoelectrophoresis, enzyme-linked immunosorbent assay and immunoturbidimetry methods. Major results. The albumin level is reliably reduced in case of IgE-mediated AD while the LF and α1-AT levels are increased, and concentrations of LF α1-AT and a2-MG are increased as compared to healthy people. There are differences between the level of LF, α2-MG and α1-AT. There was a statistically significant correlation between the LF levels and SCORAD score in both forms, and α2-MG and α1-AT only in case of IgE-independent AD. Conclusion. These results confirm the difference in the roles of these polyfunctional proteins in the pathogenesis of IgE-mediated and IgE-independent AD.